2016
DOI: 10.1155/2016/7802521
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Background of miRNA Role in Asthma and COPD: An Updated Insight

Abstract: Inflammatory airway diseases are a significant health problems requiring new approaches to the existing therapies and addressing fundamental issues. Difficulties in developing effective therapeutic strategies might be caused by lack of understanding of their exact molecular mechanism. MicroRNAs (miRNAs) are a class of regulators that already revolutionized the view of gene expression regulation. A cumulating number of investigations show a pivotal role of miRNAs in the pathogenesis of asthma, chronic obstructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 89 publications
0
33
0
1
Order By: Relevance
“…Different papers have recently demonstrated that some miRNAs are elevated in asthma and COPD patients 16. Moreover, the expression of miRNAs seems to be different in various asthma models.…”
Section: Discussionmentioning
confidence: 99%
“…Different papers have recently demonstrated that some miRNAs are elevated in asthma and COPD patients 16. Moreover, the expression of miRNAs seems to be different in various asthma models.…”
Section: Discussionmentioning
confidence: 99%
“…This disease is accompanied by the presence of chronic obstruction. [ 1 ] Multiple lines of evidence have indicated that a wide range of factors (i.e., genetical and environmental) are involved in the initiation and progression of COPD. Smoking is known as one of the main factors which could be associated with chronic inflammation of the airways.…”
Section: Introductionmentioning
confidence: 99%
“…Lowering GSL levels in mast cells in an animal model of asthma was found to ameliorate disease manifestations [ 45 ]. Both mature forms of miR-499a and miR-499b were predicted to target about 40 and 60 genes in TGF-beta and TNF signaling pathways, important mediators contributing in lung tissue fibrosis and proliferation of smooth muscle cells with subsequent airway remodeling [ 46 ]. We also identified several targets for miR-499 gene family in adherence junction and focal adhesion pathways.…”
Section: Discussionmentioning
confidence: 99%